Effect of swim cap model on passive drag - Gatta, G.; Zamparo, P.; Cortesi, M. (The Journal of Strength and Conditioning Research, 2013)
Hydrodynamics plays an important role in swimming because even small decreases in a swimmer's drag can lead to performance improvements. During the gliding phases of a race, the head of a swimmer is an important point of impact with the fluid, and the swim cap, even if it covers only a small portion of the swimmer's body, can have an influence on drag. The purpose of this study was to investigate the effects on passive drag (Dp) of wearing 3 different types of swim caps (LSC: a lycra cap; CSC: a silicone cap; HSC: a silicone helmet cap without seams). Sixteen swimmers were tested at 3 velocities (1.5, 1.7, 1.9 m/s), and the Dp measurements were repeated at each condition 5 times. A statistical analysis revealed significant differences in drag (p < 0.01) among caps: Dp is 5-6.5% lower for HSC than for CSC at all speeds and 6% lower in HSC than CSC at 1.9 m/s. No differences in Dp were observed between LSC and CSC at all speeds. Thus, the differences in Dp are based on the type of material (lycra vs. silicone) and on the presence/lack of seams: the HSC swim cap is the most rigid, the most adherent to the swimmer's head, and does not allow the formation of wrinkles compared with the other 2 investigated swim caps. Therefore, the following conclusions can be made: (a) swimmers should take care when selecting their swim cap if they want to improve the fluid dynamics at the "leading edge" of their body and (b) because Dp is affected by the swim cap model, care should be taken when comparing data from different studies, especially at faster investigated speeds.